Propose an Image Watermarking Algorithm Stand against JPEG Compression based on Space Transformation and Image Features (مجلة المنصور, 2022)
In this proposal, a new algorithm is introduced to watermarked digital images (with format BMP). After trying number of features to decide which blocks of image are the best hosts, two features DC (Direct Current) Coefficient(resulting for Discrete Cosine Transform(DCT)) and the Entropy (H) are chosen, since these features are specifying embedding locations that cause a minimal degradation to the cover image and determining the blocks that can keep the embedded value stand against compression .This algorithm produces a watermarked image that can be subjected to lossy JPEG (Joint Photographic Experts Group) compression without losing its watermark. Fidelity Criteria evaluates the errors between the original and cover images, good tests are achieved without perceptual degradation for the transparency of the cover image.